The role of mundane and subtle institutional work in market dynamics: A case of fashion clothing market - Ghaffari, Mahsa; Jafari, Aliakbar; Sandikci, Ozlem (Journal of business research, 2019)
Research on market dynamics shows that markets (trans)form through the institutional work of a wide range of actors. This literature, however, focuses on resourceful and/or powerful actors who can freely and openly shape the market. Via an inductive analysis of the Iranian female fashion clothing market, we examine the institutional work undertaken by actors who have limited resources and are subject to power structures that constrain their institutional work. We find that consumers, designers, retailers, and social activists engage in ambidextrous practices, secure networks, and stealthy defiance to navigate or moderate their institutional restrictions. Such work contributes to the relaxation of some state regulations and the coexistence of parallel taste structures. The study draws attention to mundane, subtle, and less visible and organized institutional work and extends knowledge on marketplace resistance by showing that everyday acts of resistance can function as unintentional institutional work that contributes to market dynamics.